Breast pump use amongst mothers of healthy term infants in Melbourne, Australia: A prospective cohort study. (February 2016) - Johns, Helene M.; Amir, Lisa H.; McLachlan, Helen L.; Forster, Della A.
Abstract: Objective: this paper describes the use of breast pumps amongst a group of mothers of healthy term infants in Melbourne, Australia, between birth and six months post partum. Design: a prospective cohort study; data were collected using structured questionnaires. Participants: 1003 postpartum women who had given birth to healthy infants at term were recruited from three Melbourne maternity hospitals between July 2009 and April 2011. Data were collected by face-to-face interview at recruitment and by telephone interview three and six months later. Findings: at recruitment (24 to 48 hours post partum), 60% (605/1003) of women already had a breast pump. At two weeks post partum expressing was common; 62% (290/466) of women had expressed by this time, with 40% (186/466) doing so several times a day. By six months post partum 83% (754/911) of the women had a breast pump and 40% (288/715) were expressing, although most just occasionally. The most common reasons for any expressing in the first six months were 'to be able to go out and leave the baby' (35%; 268/772); milk supply 'not enough'(27%; 207/772); and having 'too much' milk (19%; 147/772). The increasing popularity of expressing breast milk to feed infants is not driven by women returning to the workforce, as only 10% of women (80/772) expressed because they had returned to paid employment. Key conclusions and implications for practice: health professionals should be aware that in some settings breast pump use is common in the first six months, and this is not always related to maternal workforce participation. Highlights: Reports breast-feeding data from birth until six months for >900 Melbourne women. Breast pump uptake was high, most women reported expressing before eight weeks. More than a third of women expressed so they could go out – but not for work. Expressing because of maternal return to paid employment was rare.